WOMEN EDUCATION IN NIGERIA: PROBLEMS AND IMPLICATIONS FOR FAMILY ROLE AND STABILITY - Uzoma Aja-Okorie (European Scientific Journal, ESJ, 2013)
Education helps men and women claim their rights and realize their potential in economic, political and social arenas. It is also the single most powerful way to lift people out of poverty. Yet, many people — especially women — are still excluded from education in Nigeria. Education should be an intrinsic part of any strategy to address the gender-based discrimination against women and girls that remains prevalent in our society. Hence, this paper offers an overview of women education in Nigeria and its benefits to women, families and the society as a whole. It highlights the ongoing concerns about education in Nigeria. The paper further examines education's links with family responsibilities and employment, two important elements in women's empowerment.